Hexagonal structure impeded intellectual youth for the advancement of civilization duty and mechanisms to address them - رياض سعيد رشيد (College of Education for Women, 2019)
Photos of the backwardness of the Muslims and their backwardness in creating sustainable development policies have driven them to a state of civilization , which witnesses Avckaddoha time ago and not disrupt the adversary is a phenomenon thought the youth to exercise its role and duty in the construction and development of the state witnesses Mdanah civilized nation. The vigilance thought the youth of its slumber correct form could provide opportunities for growth and development in the Arab and Islamic worlds, and both material and moral support through the creation model youth Islamic social role models, but that the image of the model , , - 1